Sequence-Based Characterization of Intratumoral Bacteria—A Guide to Best Practice - Walker, Sidney P.; Tangney, Mark; Claesson, Marcus J. (Frontiers in Oncology, 2020)
Tumours are hospitable environments to bacteria and several recent studies on cancer patient samples have introduced the concept of an endogenous tumour microbiome. For a variety of reasons, this putative tumour microbiome is particularly challenging to investigate, and a failure to account for the various potential pitfalls will result in erroneous results and claims. Before this potentially extremely medically-significant habitat can be accurately characterised, a clear understanding of all potential confounding factors is required, and a best-practice approach should be developed and adopted. This review summarises all of the potential issues confounding accurate bacterial DNA sequence analysis of the putative tumour microbiome, and offers solutions based on related research with the hope of assisting in the progression of research in this field.